Creep strain rates analysis in cylinder under temperature gradient materials by using Seth's theory. Issue 3 (2nd May 2017) - Thakur, Pankaj; Gupta, Nishi; Bir Singh, Satya
Abstract : Purpose: The purpose of this paper is to present study of creep strain rates in a circular cylinder under temperature gradient materials by using Seth's transition theory. Design/methodology/approach: Seth's transition theory is applied to the problem of creep stresses and strain rates in a cylinder under temperature gradient materials by finite deformation. Neither the yield criterion nor the associated flow rule is assumed here. The results obtained here are applicable to compressible materials. If the additional condition of incompressibility is imposed, then the expression for stresses corresponds to those arising from Tresca yield condition. Findings: Thermal effect increases the values of axial stress at the external surface of a circular cylinder for incompressible material as compared to compressible materials. With the introduction of thermal effects, the maximum value of strain rates occurs at the external surface for incompressible material as compared to the compressible materials. Originality/value: The model proposed in this paper is used commonly either as pressure vessels intended for storage industrial gases or media transportation of high pressurized fluids and the design of turbine rotors.